2002
DOI: 10.1080/00224540209603894
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation Attitudes, Need for Cognitive Closure, and Adaptation of Immigrants

Abstract: The author validated Berry's model of acculturation (J. W. Berry, 1990a, 1990b, 1991; J. W. Berry, U. Kim, S. Power, M. Young, & M. Bujaki, 1989) and examined the relation between acculturation attitudes and sociocultural and psychological adaptation among Croatian and Polish immigrants to Italy, 2 groups whose cultures are not very different from the Italian culture. Moreover, the author investigated the relation between the need for cognitive closure (NCC; M. D. Webster & A. W. Kruglanski, 1994) and psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 34 publications
2
43
0
6
Order By: Relevance
“…However, acculturation researchers who have been quick to cite Berry have been less than precise in their operationalization of his two defining issues. Indeed, Matsudaira's (2006) review of acculturation measures, which identified 51 acculturation scales published between 1978 and 2004, cited only one instrument that captured the essence of Berry's dimensions - Kosic's (2002) Scale of Acculturation Strategies with Maintenance of Original Culture and Relationships with Host Group subscales. Liebkind (2001) summarized the modifications of Berry's (1980) cultural maintenance and contact model, noting that some researchers have conceptualized acculturation in terms of cultural maintenance and cultural adoption (e.g., Bourhis, 1 Berry added a third question in his 1974 and 1980 papers: "whether the minority groups are permitted the option of answering the first two questions?"…”
Section: Introductionmentioning
confidence: 99%
“…However, acculturation researchers who have been quick to cite Berry have been less than precise in their operationalization of his two defining issues. Indeed, Matsudaira's (2006) review of acculturation measures, which identified 51 acculturation scales published between 1978 and 2004, cited only one instrument that captured the essence of Berry's dimensions - Kosic's (2002) Scale of Acculturation Strategies with Maintenance of Original Culture and Relationships with Host Group subscales. Liebkind (2001) summarized the modifications of Berry's (1980) cultural maintenance and contact model, noting that some researchers have conceptualized acculturation in terms of cultural maintenance and cultural adoption (e.g., Bourhis, 1 Berry added a third question in his 1974 and 1980 papers: "whether the minority groups are permitted the option of answering the first two questions?"…”
Section: Introductionmentioning
confidence: 99%
“…In regard to the adaptation process, various group-level, situational and individual factors have been examined by many researchers throughout the years; specifically age (Leung 2001;Yeh and Inose 2003), gender (Jingyun 1999;Lee 1999), status (Aycan and Berry 1996;Shen and Takeuchi 2001), cultural distance maintained (Phalet and Hagendoorn 1996;Searle and Ward 1990), personality (Padilla et al 2001;Ward and Kennedy 1993), length of time involved (Guan and Dodder 2001;Zhang and Rentz 1996), language proficiency (Poyrazlı et al 2001), acculturation attitudes (Ataca and Berry 2002;Eshel and Rosenthal-Sokolov 2000;Kosic 2002), coping attitudes (Mena et al 1987), social support (Chung et al 2000;Miranda and Matheny 2000;Ward and Rana-Deuba 2000), and discrimination (Ataca and Güroğlu 2002;Liebkind and Jasinskaja-Lahti 2000).…”
mentioning
confidence: 99%
“…Many studies have focused on migrants' adaptation to different cultures across different settings, such as in schools, workplaces, and in the community (see Kosic, 2002;Matsunaga, echt, Elek, & Ndiaye, 2010;Shalom & orenczyk, 2004). owever, such studies are still limited, particularly in community garden settings, despite the current discussion on advantages of involvement in community gardens for immigrants (such as in Baker, 2004;Bartolomei, Corkery, Judd, & Thompson, 2003).…”
Section: Introductionmentioning
confidence: 99%